REGIONAL SPECIFICS OF THE LEVEL AND STRUCTURE OF MORTALITY CAUSES AMONG WOMEN OF REPRODUCTIVE AGE IN AZERBAIJAN - Baghirova, L.G. (World of Medicine and Biology, 2025)
The observation was carried out in 11 districts. The frequency (level) was determined mortality of 100,000 women of the corresponding ages and the proportion of causes of death (per 100 deaths from all causes).In the regions of Azerbaijan, the indicator ranges from 44.4±7.4 to 79.2±7.80⁄0000 and differs from each other (p=0.05). The lowest mortality rate was observed in the Absheron and Mountainous-Shirvan economic regions. When comparing the indicators of the regions with the lowest mortality rate, Shirvan-Salyan (79.2±7.80⁄0000), Ganja-Dashkesan (72.5±6.80⁄0000), Gazakh-Tovuz (67.4±6.20⁄0000), Karabakh (67.5±7.30⁄0000), Central Arran (57.6±5.60⁄0000), Mil-Mugan (62.8±6.90⁄0000) and Astara-Lankaran (59.0±4.90⁄0000) economic regions. With the age of women, the risk of mortality increases, its lowest level was at the age of 15–19 years (22.9±3.50⁄0000 total by region, 9.05±5.2–34.6±1.310⁄0000 the range of fluctuations is in certain regions), and the largest is at the age of 40–49 years (respectively 118.9±5.90⁄0000; 80.5±11.2–172.9±23.10⁄0000).
Keywords: regional specificities; level; structure; cause of mortality; women of reproductive age